Bioterrorism in the Twenty-First Century: Exploring the Threat of Potential use of Biological Weapons by Anti-State Agents - Umar, Ayesha (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
Bioterrorism involves the intentional dissemination of biological agents, such as bacteria, viruses, toxins, or fungi, with the aim of causing widespread fear, illness, and death among targeted populations. Anti-state agents, including terrorist organizations or individuals with extremist ideologies, may employ bioterrorism as a means to achieve their political, ideological, or religious objectives. The study explores the motivation behind the potential use of bioterrorism by anti-state agents, the threat of biological warfare, and the state readiness in the case of a biological attack. It examines the history of biological warfare, the factors that make biological warfare attractive to terrorist organizations including potential for mass casualties, psychological factors behind the attacks, access of biological agents, and the issues and challenges associated with detection, responses, and prevention of a biological attack by anti-state agents. The research used securitization theory to understand the phenomenon behind biological warfare. The study identified that despite the small scale of biological attacks in the past by anti-state agents, the threat has increased in the recent times as the technological advances and access to these agents make the people vulnerable to such attacks by the non-state actors . The study also concluded that strengthening global surveillance systems, enhancing public health infrastructure, and promoting information sharing among states and international emergency response services are vital in preventing and mitigating the impact of bioterrorist attacks.